2019
DOI: 10.1186/s13098-019-0479-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D supplementation on advanced glycation end products signaling pathway in T2DM patients: a randomized, placebo-controlled, double blind clinical trial

Abstract: BackgroundSeveral researches have recommended vitamin D possible health benefits on diabetic complications development, but a few number of studies have been accomplished on the molecular and cellular mechanisms. Certain cellular pathways modification and also some transcription factors activation may protect cells from hyperglycemia condition induced damages. This study purpose was to determine the vitamin D supplementation effect on some key factors [advanced glycation end products (AGEs) signaling pathway] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The VDRAs beneficial effects have been also described in the diabetic nephropathy due to the links between VDRAs and the glucose metabolism through the upregulation of the glucose transporter 4 (GLUT4) [ 175 ] and insulin secretion [ 176 ]. Moreover, a recent meta-analysis of randomized controlled trials found that supplementation with VDRAs to type-2 diabetic patients may reduce inflammation [ 177 ], down-regulating RAGE gene expression in peripheral blood mononuclear cells and decreasing serum AGES and TNF-α levels [ 178 ]. In addition to the protective anti-inflammatory effect of VDRAs on the diabetic nephropathy, several clinical and experimental studies have attributed to the VDRAs a role in the control of the progression of diabetic nephropathy, mainly through their combined effects on the RAS, inflammation, and suppression of the renal tubular EMT.…”
Section: Vitamin D and Ckd Fibrosismentioning
confidence: 99%
“…The VDRAs beneficial effects have been also described in the diabetic nephropathy due to the links between VDRAs and the glucose metabolism through the upregulation of the glucose transporter 4 (GLUT4) [ 175 ] and insulin secretion [ 176 ]. Moreover, a recent meta-analysis of randomized controlled trials found that supplementation with VDRAs to type-2 diabetic patients may reduce inflammation [ 177 ], down-regulating RAGE gene expression in peripheral blood mononuclear cells and decreasing serum AGES and TNF-α levels [ 178 ]. In addition to the protective anti-inflammatory effect of VDRAs on the diabetic nephropathy, several clinical and experimental studies have attributed to the VDRAs a role in the control of the progression of diabetic nephropathy, mainly through their combined effects on the RAS, inflammation, and suppression of the renal tubular EMT.…”
Section: Vitamin D and Ckd Fibrosismentioning
confidence: 99%
“…Third, vitamin D deficiency leads to vascular endothelial dysfunction. Studies have shown that 1,25 dihydroxy vitamin D [1,25(OH)2 D] reduces the deleterious effects of advanced glycation end product on the endothelium 34,35 . Furthermore, vitamin D improves the activity of the nitric acid system and reduces inflammatory and atherosclerotic factors, and its deficiency is a risk factor for hypertension 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D was also reported to exert a protective role against glycative stress [210,211]. Vitamin D supplementation in type-2 diabetes participants showed a trend in increasing GLO1 expression, a transcriptional downregulation of RAGE receptor and decreased in AGE serum in a double-blind randomized placebo-controlled [211]. Nevertheless, the action of vitamins remains controversial because vitamin-treatment had no significant impact in other studies.…”
Section: Vitaminsmentioning
confidence: 99%